Genital Ambiguity and Assignment of Sex - a Case Report - Chowdhury, ATM Mowladad; Rahman, Shafiqur; Aziz, Mohammad Abdul; Hasan, Mirza Mahbubul; Happy, Nurunnahar (Bangladesh Journal of Urology, 2020)
A 15 year patient having 46XX karyotype, along with well developed male type of external genitalia and developing breast reported to us. It was assessed on all technical and judicious points and the male sex was assigned. Bangladesh Journal of Urology, Vol. 18, No. 2, July 2015 p.98-99